"A little more complex": pro bono commitment in São Paulo corporate law firms. Issue 3 (2nd September 2021) - Fabio, de Sa e Silva
ABSTRACT: Pro bono's development in São Paulo, Brazil, has been a conflictive process, resisted by multiple segments in the legal profession. In 2001, this conflict led the São Paulo State Bar to impose regulatory restrictions on pro bono practice. One of these restrictions involved pro bono services to individuals, which firms or any other practitioner were explicitly prohibited from delivering. In 2015, this changed radically. The bar removed most of its restrictions to pro bono. Many expected that this would cause firms to further their commitment to pro bono and, more specifically, to start offering free legal services to needy individuals. This expectation, however, was not met. In the absence of regulatory restrictions, what explains the decision by São Paulo corporate law firms of whether or not to engage in the provision of individual pro bono services? Based on multiple data sources and a multi-staged empirical research process, this article points to a set of institutional forces and cognitive frames that have shaped the development of pro bono in such firms post-2015. These include law firm organizational rationality, "turf wars" over legal aid work, and lawyers' professional idealism.